The Effectiveness of Back Totok as a Natural Labor Induction in Third Trimester Pregnant Women at PMB Afah Fahmi, Amd.Keb - Khairoh, Miftahul; Rosyaria, Arkha (Jurnal Midpro, 2022)
Cinnamon, Episiotomy Wound Pain, Post Partum Mother. Episiotomy wound pain is a normal condition that occurs in post partum mothers who have sutured procedures. The aim of the study was to determine the effectiveness of giving cinnamon (Cinnamomun Verum) decoction to reduce episiomotomy wound pain in the PMB Istiqomah Region, SST.,M.Kes. Pre Experimental research method with Pretest and Posttest approach Without Control Group design. The actual population in this study were all post partum mothers in the PMB Istiqomah area, SST.,M.Kes. The target population is all postpartum mothers from the first day to 7 days at PMB Istiqomah SST.,M.Kes. The sampling technique was purposive sampling as many as 11 postpartum mothers, hypothesis analysis using McNemar test. The results of the study: the age characteristics of the respondents were mostly 20-35 years, the number of parity was mostly parity 1, the occupations were mostly housewives and. Episiotomy wound pain in post partum mothers before being given cinnamon decoction in the PMB Istiqomah area SST., M.Kes as many as 10 people (90%) had pain. Episiotomy wound pain in post partum mothers after being given cinnamon decoction in the PMB Istiqomah area SST., M.Kes as many as 9 people (80%) The pain is reduced. Mc Nemar test results using SPSS obtained a significant value (Ï) 0.000 <0.04. So based on the research hypothesis, it can be concluded that if Value <0.05 then Ho is rejected, Ha is accepted, which means that there is an effectiveness of cinnamon (cinnamomun verum) decoction on reducing episiotomy wound pain